2018
DOI: 10.1007/s11096-018-0679-8
|View full text |Cite
|
Sign up to set email alerts
|

A simulated patient study assessing over the counter supply and counseling in Jordan: responding to headache complaints

Abstract: Background Community pharmacists are the most accessible health professionals for patients seeking advice on minor ailments and over the counter supply. Objectives To assess the management of patients seeking advice for headache in community pharmacies in Jordan. Method A cross-sectional study was conducted using simulated patient in three cities in Jordan. A trained simulated patient enacted an advice-seeking scenario for the treatment of a headache. The visits were evaluated using pre-defined criteria relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
50
1
8

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(62 citation statements)
references
References 8 publications
3
50
1
8
Order By: Relevance
“…Other published papers show even a larger variability in the results obtained in the same health problem e.g. headache (Hammad et al, 2018, Horvat et al, 2012). The most frequently provided information was dosage and the price of the medicine.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Other published papers show even a larger variability in the results obtained in the same health problem e.g. headache (Hammad et al, 2018, Horvat et al, 2012). The most frequently provided information was dosage and the price of the medicine.…”
Section: Discussionmentioning
confidence: 93%
“…A wide range of counselling success, the counselling absence or various deficiencies in counselling have been identified in other published studies, while using the mystery shopping method (Alaqeel and Abanmy, 2015, Alfadl et al, 2017, Berger et al, 2005, Hammad et al, 2018, Horvat et al, 2012, Negru et al, 2012, Paravattil et al, 2017, Santos et al, 2013). Considering the total Counselling Performance, we can conclude that counselling on self-medication of common cold in Slovak pharmacies had a suboptimal level (39.0 ± 22.4%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding concurs with existing literature. In a study on pharmacists’ recommendations in Jordan for over the counter medications for headache, medication recommendations were frequently made without obtaining essential information about the SP’s symptoms or medical history [ 18 ]. This also occurred in a community pharmacy SP study in Australia with smoking cessation [ 1 ].…”
Section: Main Textmentioning
confidence: 99%
“…Previous research in Jordan outlined that pharmaceutical care services are often limited and pharmacists in community settings do not collect sufficient information about patient medical history [1317]. These studies, however, relied on self-reported questionnaires by pharmacists or patients with limited or no direct observation of the actual content and the nature of the interaction between the pharmacist and the patient in real situations.…”
Section: Introductionmentioning
confidence: 99%